Segmentation of ultraviolet-dermatoscopic images - Isaieva, O. A.; Avrunin, O. G.; Ісаєва, О. А.; Аврунін, О. Г. (Perfect Publishing, Vancouver, Canada., 2020)
Based on the UV dermoscopy method, using the SkinScope device, images of the skin of a person’s face are examined. The color systems that are used in the evaluation of images in UV dermoscopy are considered. It is proposed to evaluate the UV-dermoscopic images using the method of transition from the RGB system to the HSV system. The basic concepts of UV-dermoscopic image segmentation are being studied. The analysis of segmented images is considered.
Keywords: video dermatoscopy; segmentation; color characteristics; image processing; color systems